ANALYSIS OF THE ACCEPTANCE OF THE SINAGA ATTENDANCE APPLICATION AT SMA NEGERI 1 JATILAWANG USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Sabaniyah, Arbangi Puput; Yunita, Ika Romadhoni; Subarkah, Pungkas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
This study analyzes the acceptance of teachers and ASN employees of the SINAGA (Sistem Informasi Layanan Kepegawaian) attendance application at SMA Negeri 1 Jatilawang using a modified Technology Acceptance Model (TAM). The model was extended by incorporating two external variables: Information Quality and Complexity. This explanatory quantitative research employed the Structural Equation Modeling–Partial Least Square (SEM-PLS) method involving 60 respondents who are civil servants, consisting of teachers and administrative staff. The results reveal that Information Quality has a positive and significant influence on both Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), while Complexity does not show a significant effect on either variable. Furthermore, PEOU and PU have a positive impact on Attitude Toward Use (ATU), which subsequently affects Behavioral Intention to Use (BIU). Behavioral intention, in turn, strongly influences Actual Use (AU). These findings indicate that teachers’ acceptance of the SINAGA digital attendance system in educational settings is primarily driven by information quality and users’ positive attitudes rather than by system complexity. Theoretically, this study contributes to the expansion of TAM application in the educational context. Practically, it provides valuable insights for improving the effectiveness of SINAGA implementation through better information quality and enhanced user experience.